EFEKTIFITAS ASUHAN BERPUSAT PADA KELUARGA DALAM KELAS ANTENATAL TERHADAP PENURUNAN STRES WANITA HAMIL - Kurniaty Ulfah; Yuni Nurchasanah (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2023)
Stress in pregnancy is closely related to the incidence of preterm labor. The estimated rate of preterm birth in Indonesia is 15.5%. Preventive efforts are needed to reduce women's stress levels during pregnancy. One such effort is family-centered care. The research results show that implementing this model can increase patient satisfaction and care outcomes and reduce anxiety and stress. However, its application in pregnancy care in Indonesia is still limited. This study aimed to determine the effectiveness of implementing family-centered care (FCC) in antenatal classes on reducing stress in women during pregnancy. This research was a quasi-experimental design with pre and post-test with control. The sample size of pregnant women for each group was 44. The sampling technique was carried out consecutively. The Revised Prenatal Distress Questionnaire (NuPDQ) measured pregnant women's stress. Data processing was done computerized with SPSS. Data analysis used a nonparametric test. This study's results indicated no significant difference in reducing the stress level of pregnant women between the groups that attended FCC antenatal classes and the control group (p>0.05). It was thought to be due to less than optimal support from husbands during antenatal classes and pregnant women in the research sample have a low risk of stress during pregnancy. Further research is needed regarding the effectiveness of FCC antenatal classes in groups of pregnant women at higher risk of experiencing stress/anxiety/depression.